PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUESTION STUDENT HAVE (QSH) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI SMA NEGERI 5 PEKANBARU - Chadmelia Igga Mustika Igga Mustika; Erviyenni '; Maria Erna Maria Erna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The research on application of cooperative learning model Question Student Have (QSH) has been done to improve of student achievement on the subject of solubility and solubility product in class XI SMAN 5Pekanbaru. Form of the research is experimental research with pretest-posttest design. The sample consist of two classes, namely class XI IPA 4 as the experimental and class XI IPA 5 as control class which randomly selected after had tested normality and homogeneity. Experiment class was given implementing cooperative learning model Question Student Have (QSH) while the control class was not given implementing cooperative learning model Question Student Have (QSH). Data analysis technique used the t-test. Based on the result of the final data processing t-test formula obtained tarithmetic>ttable (2,258  > 1,67) means the application of cooperative learning model Question Student Have (QSH) can improve student achievement on the subject of solubility and solubility product in class XI SMAN 5Pekanbaru, with an increase of 6,53%. Key Words: Question Student Have (QSH), Learning achievement, Solubility and solubility product.